Topology Optimization of Acetabular Cup by Finite Element Simulation - Abdullah, Muhammad Ahmed (International Journal of Engineering and Management Sciences, 2020)
Hip replacements typically consist of a four-part piece. Our research will focus primarily on the acetabular component. Several different types of materials can be used when creating a hip replacement implant ranging from plastic to titanium. Different materials are used to accommodate for allergic reactions or circumventing potential health risks. Aside from the material, the size of the components plays a factor in terms of durability; a larger diameter head might avoid dislodgement though it could increase wear and tear on the stems through constant friction. A patient’s force applied to the hip replacement is usually measured through a number of physical assessments. Finite element analysis (FEA), a computer-based method of data observation, allows for us to accurately simulate hip forces and their impact on the hip replacements. Through this, it becomes easier to predict and calculate the performance of specific designs. Generative systems can also be used to support performance analysis and optimization through assessing a multitude of cases, many of which apply in real-world scenarios. By applying both systems, we designed and modeled an acetabular cup that when measured decreased the mass from 129 grams initially down to 52 grams, a 60% decrease in total mass. Furthermore, the design we created lessened the trauma on the piece through distributing force across the entirety of the piece rather than specific segments only. This shows an increased durability and life expectancy when compared to usual acetabular cups.